Ijtihad Jama’i sebagai Metode Penetapan Fatwa Produk Halal (Studi Analisis terhadap Konstruksi Elite Ulama Bangkalan) - Amaroh, Siti Tholik; Holis, Holis (Global Education Journal, 2023)
Progress over time in various sectors of life has given rise to various contemporary Islamic legal issues that cannot be answered with qat'i texts. Therefore, Islamic legal issues must involve a wide variety of scientific experts known as ijtihad jama'i (collective). This research aims to find out the importance of the concept of jama'i ijtihad in relation to the method of determining fatwa on halal products, to understand the views of Bangkalan elite kiai regarding jama'i ijtihad as a method of determining fatwa on halal products, and to find out the pattern of application of the concept of jama'i ijtihad i as a method for determining product halal fatwa. This research is qualitative research with an inductive method. This research focuses on collecting data through interviews, documentation and conducting field surveys by interviewing several elite ulama in the Bangkalan area. This qualitative method will be descriptive in nature and aims to provide a complete explanation and picture regarding Ijtihad Jama'i. The results of this research show that jama'i ijtihad is very important to apply as a method for determining fatwa on halal products. This is because the process of implementing jama'i ijtihad is carried out by several experts from several fields of science. So, in the process of determining a product halal fatwa, the halal percentage of a product is more guaranteed because when a product is tested by several scientific experts, it is guaranteed to be correct, compared to only being tested by one person.